2009
DOI: 10.1177/0363546509340407
|View full text |Cite
|
Sign up to set email alerts
|

Independent Drilling Outperforms Conventional Transtibial Drilling in Anterior Cruciate Ligament Reconstruction

Abstract: Single-bundle anterior cruciate ligament reconstructions will be improved if grafts are centered in their anatomical insertions by an independent drilling method versus grafts placed by a conventional transtibial drilling method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(168 citation statements)
references
References 53 publications
2
162
1
3
Order By: Relevance
“…Some recent anatomical studies 2,4 have shown that is not possible to reach the ACL center using the transtibial technique. To reach the center using the transtibial technique, an extremely horizontal tibial tunnel is necessary, with risk of the tunnel being short and subchondral 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent anatomical studies 2,4 have shown that is not possible to reach the ACL center using the transtibial technique. To reach the center using the transtibial technique, an extremely horizontal tibial tunnel is necessary, with risk of the tunnel being short and subchondral 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported similar outcomes between transtibial and anteromedial portal techniques 9,10 . Despite these studies, most studies comparing the transtibial technique with anatomical techniques (anteromedial portal or "outside-in") reported superior outcomes (objective and subjective) with the anatomical techniques 2,[5][6][7]11 . A precise technical guidelines for the transtibial and anteromedial portal techniques was published 18 , stating that it is possible to drill similar tunnels using both techniques as long as the anatomical parameters and guide angles are respected; however, the advantage of the transtibial technique is not requiring knee hyperflexion, which hinders the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,8,12,17,20,21,33 Recent literature has suggested that oblique, anatomically placed femoral tunnels more accurately restore normal knee biomechanics, particularly with simulated Lachman and pivot-shift testing. 1,15,28,37,38 Many surgeons are therefore choosing independent femoral tunnel drilling techniques to achieve a more anatomic graft placement and thus are creating more obliquely oriented tunnels. However, in skeletally immature patients, utilizing an independent drilling technique may result in the femoral tunnel being placed more eccentrically across the distal femoral physis, exiting closer to the perichondrial ring, and potentially drilling across a larger area of the physis, thus increasing the potential risk of physeal damage.…”
mentioning
confidence: 99%
“…The restoration of the anatomy of the knee to the nearest normal, with the positioning of the tunnels in the most anatomically possible position, is crucial to the success of ACL reconstruction [19][20][21][22][23] . Most articles study the anatomy of the ACL as a whole, not analyzing the bands separately, which constitutes a limiting factor in studying the placement of tunnels with dual band reconstruction.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%